Re-Defining Sustainable Mobility – A Sensemaking perspective - Nyström, Johan (My University, 2019)
Transport has many issues known today: congestion, pollution, traffic accidents leading to deaths, noise, and loss of urban space. Many nations suffer for similar problems, which suggest there is not a solution for the problem. Transition management is a governance approach which purpose is to accelerate sustainability transitions by a participating process of visioning, learning and experimenting. Furthermore, Transition Management brings together several perspectives and approaches in a “transition arena”. Actors are brought together to develop the current system and to construct shared visions and goals. This study seeks to find you how actors re-define sustainable mobility. Also, via the usage of sensemaking theories extending the understanding of the collective phenomenon of the envisioning process of the desired shared visions. A conceptual framework is built combining the transition management theories together with sensemaking to form the backbone for this study. A qualitative case study was conducted via the transition arena. Data was carefully analyzed to understand the relation to sensemaking theories. The phenomenon can be organized into thought that gives actual knowledge on what is ongoing. With the process of enactment-selection-retention and process of understanding what is going on. Grouping the collective sensemaking might help to see patterns of interlocking behaviors. Results indicate that via the sensemaking processes the whole phenomena's uncertainty can be lowered to a degree where it is possible to create a plausible story. Furthermore, in this phase it is enabled to create processes and systems, this can be used to give further understanding to the whole phenomenon. Lastly the sensemaking theories implies the need for enhancing the communication within the societal system.
Keywords: Transition management; sustainability; mobility; sensemaking; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|